A research on effect of certificate trainings on pre-service teachers' awareness of psychological resilience - Çankaya, Ibrahim; Balikçi, Servet; Bek, Hafiz (Edelweiss Applied Science and Technology, 2025)
The aim of this research is to determine whether certification training has a significant effect on pre-service teachers' awareness. In the research, the awareness level of pre-service teachers who participated in psychological resilience training was compared. The research is a one-group pre-test post-test quasi-experimental research design. The research group consisted of 25 pre-service teachers who participated in the psychological resilience trainings organized by Uşak University Lifelong Learning Center in the spring semester of the 2024-2025 academic year. The research group received resilience awareness training consisting of two sessions and lasting 1.5 weeks. Data were collected using the brief psychological resilience scale developed by Doğan. It was determined that there was a significant difference (p < .05) between the psychological resilience awareness levels of the students before and after the certificate training. In the 21st century, certificate trainings will be provided in addition to the university diploma in order to provide the skills that institutions and the business world care about. Certificates will be among the primary reasons for teacher selection.